1988
DOI: 10.1530/jrf.0.0830803
|View full text |Cite
|
Sign up to set email alerts
|

The acute-phase response in endometriosis of women

Abstract: Summary. Peritoneal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…However, Dunselman and coworkers demonstrated that small proteins with a molecular weight <40 kDa could readily move between the vasculature and the peritoneal fluid [31]. Intraperitoneal injection with interleukin (IL)-4 was able to inhibit basic fibroblast growth factor (bFGF)-induced corneal neovascularization [32].…”
Section: Induction Of Angiogenesis In the Peritoneummentioning
confidence: 99%
“…However, Dunselman and coworkers demonstrated that small proteins with a molecular weight <40 kDa could readily move between the vasculature and the peritoneal fluid [31]. Intraperitoneal injection with interleukin (IL)-4 was able to inhibit basic fibroblast growth factor (bFGF)-induced corneal neovascularization [32].…”
Section: Induction Of Angiogenesis In the Peritoneummentioning
confidence: 99%
“…Small molecules, such as urea and electrolytes, diffuse rapidly. Diffusion rates decrease with the molecular weight and become slow for molecules larger than 100,000 as molecular weight [30]. From this it can be anticipated that the concentrations of small molecules in peritoneal fluid and plasma are similar, whereas the concentrations of larger molecules from the blood stream are lower in peritoneal fluid.…”
Section: Introductionmentioning
confidence: 95%
“…The increasing level of CRP and ESR in pelvic peritoneum due to inflammation process can also be detected in blood serum. 12 However, measurement of CRP and ESR from our research did not appear to be advantageous for determining the severity of endometriosis. There was no association between CRP level and stage of the disease.…”
Section: Discussionmentioning
confidence: 60%
“…11 Although the pathogenesis of endometriosis is still controversial, growing evidence indicate a significant role of inflammatory factors involved in the development of endometriosis. 12,13 Biomarker such as CRP and ESR are acute phase proteins that increased when inflammation occurs. It has been suggested that in women with endometriosis there is an inflammatory reaction of the pelvic peritoneum.…”
Section: Discussionmentioning
confidence: 99%